Peru : Staff Report for the 2002 Article IV Consultation, First Review Under the Stand-By Arrangement, and Request for Modification and Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines Peru's 2002 Article IV Consultation, First Review Under the Stand-By Arrangement, and a Request for Modification and Waiver of Performance Criteria. The fiscal policy was tightened in early 2002 from the expansionary stance in the second half of 2001. The baseline medium-term outlook is favorable, albeit not without risks. Assuming sound macroeconomic policies and structural reforms continue, Peru should be able to achieve medium-term growth of 5 percent. However, the domestic political situation contains clear risks, potentially holding up tax reform and undermining fiscal discipline.